Work-Life Balance, Employee Well-Being, and Organizational Performance in Digital Startups in Greater Jakarta - Flora Grace Putrianti Putrianti; Sukmarani Sukmarani; Yumhi Yumhi; Maesaroh Maesaroh; Andri Susilo (West Science Journal Economic and Entrepreneurship, 2026)
The rapid expansion of digital startups in Greater Jakarta has intensified the need for effective human resource strategies that support both employee well-being and organizational performance. This study aims to examine the relationships between work–life balance, employee well-being, and organizational performance using a quantitative approach. Data were collected from 150 employees working in digital startup environments through a structured questionnaire measured on a five-point Likert scale. Statistical analysis was conducted using SPSS version 25, including descriptive statistics, reliability testing, classical assumption tests, and multiple regression analysis. The results indicate that work–life balance has a significant positive effect on employee well-being, while both work–life balance and employee well-being significantly influence organizational performance. Employee well-being also acts as an important mechanism that strengthens organizational outcomes by enhancing motivation, emotional stability, and engagement. The findings highlight the strategic role of flexible work practices and supportive organizational culture in sustaining productivity within fast-paced digital startup contexts. This study contributes to the organizational behavior literature by providing empirical evidence from emerging digital economies and offers practical insights for startup leaders in designing human-centered workplace policies that promote sustainable performance.